Effect of window length when smoothing with singular spectrum analysis technique in running data - Ishimura, K.; Sakurai, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to demonstrate the effect of window length on running kinematic data in comparison to data smoothed using a digital Butterworth low pass filter. The raw marker trajectories were smoothed using a digital Butterworth filter with an optimum cutoff frequency and using the SSA technique with window lengths of L = n/2, n/5, and n/10 (n = 220). Data smoothing using SSA parameters of L = n/10, r = 2 produced similar results to the Butterworth low pass filter with an optimal cutoff frequency of 13 Hz. In conclusion, a window length of L = n/10 is recommended for running kinematics research, while window lengths of L = n/2 should be avoided.